Tfs1p, a Member of the PEBP Family, Inhibits the Ira2p but Not the Ira1p Ras GTPase-Activating Protein in Saccharomyces cerevisiae - Chautard, Hélène (American Society for Microbiology, 2004)
Ras proteins are guanine nucleotide-binding proteins that are highly conserved among eukaryotes. They are involved in signal transduction pathways and are tightly regulated by two sets of antagonistic proteins: GTPase-activating proteins (GAPs) inhibit Ras proteins, whereas guanine exchange factors activate them. In this work, we describe Tfs1p, the first physiological inhibitor of a Ras GAP, Ira2p, in Saccharomyces cerevisiae. TFS1 is a multicopy suppressor of the cdc25-1 mutation in yeast and corresponds to the so-called Ic CPY cytoplasmic inhibitor. Moreover, Tfs1p belongs to the phosphatidylethanolamine-binding protein (PEBP) family, one member of which is RKIP, a kinase and serine protease inhibitor and a metastasis inhibitor in prostate cancer. In this work, the results of (i) a two-hybrid screen of a yeast genomic library, (ii) glutathione S-transferase pulldown experiments, (iii) multicopy suppressor tests of cdc25-1 mutants, and (iv) stress resistance tests to evaluate the activation level of Ras demonstrate that Tfs1p interacts with and inhibits Ira2p. We further show that the conserved ligand-binding pocket of Tfs1—the hallmark of the PEBP family—is important for its inhibitory activity.